Algorithmic Visibility and Entrepreneurial Survival in Hospitality: A Structural Equation Model of Communication Adaptation and Trust Among Micro, Small, and Medium Enterprises - Prasetya Yoga Santoso; Ressa Uli Patrissia (Dinasti International Journal of Education Management and Social Science, 2026)
The viability of micro, small, and medium enterprises (MSMEs) in Indonesia's hospitality sector is increasingly contingent upon the capacity of entrepreneurs to navigate algorithm-driven digital ecosystems that govern audience reach, reputation, and demand. Despite the proliferation of platform-mediated commerce, empirical models that articulate how algorithmic visibility translates into entrepreneurial survival remain scarce, particularly within the Global South. This study addresses that gap by developing and empirically validating the Algorithmically Mediated Hospitality (AMH) model, which posits algorithmic visibility as an antecedent of entrepreneurial survival operating through the sequential mediation of communication adaptation and customer trust, and conditioned by digital literacy. Drawing on the Resource-Based View (J. Barney, 1991), Adaptive Communication Theory (Daft & Lengel, 1986), and the platform-economy literature (Cusumano et al., 2019), the model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) on cross-sectional survey data collected from 287 hospitality MSME owners (boutique hotels, cafés, and homestays) in Jakarta, Bali, Yogyakarta, and Bandung. The results indicate that algorithmic visibility exerts a statistically significant positive effect on communication adaptation (β = 0.612, p < .001), customer trust (β = 0.431, p < .001), and entrepreneurial survival (β = 0.278, p < .001). The sequential indirect effect was confirmed (β = 0.189; 95% CI [0.134, 0.251]), and digital literacy significantly moderated the algorithmic visibility–communication adaptation pathway (βinteraction = 0.214, p < .001). The model accounts for 53.1% of the variance in entrepreneurial survival, exceeding benchmarks reported in comparable Southeast Asian SME studies (Fauzi et al., 2023). Theoretically, the study contributes a measurement-validated construct of algorithmic visibility and extends the Resource-Based View into platform-mediated competition. Practically, the findings inform a redesign of national MSME digital-literacy policy that explicitly incorporates algorithmic literacy as a survival-relevant competence.